Metal-dependent cell death resistance contribute to lymph node metastasis of oral squamous cell carcinoma - Liu, Xuan-Hao; Wang, Guang-Rui; Zhong, Nian-Nian; Zhu, Zheng-Rui; Xiao, Yao; Li, Zheng; Bu, Lin-Lin; Liu, Bing (Frontiers in Cell and Developmental Biology, 2025)
ObjectivesFerroptosis and cuproptosis can be summarized as metal-dependent cell death. This study aimed to explore the expression of metal-dependent cell death resistance (MCDR) characteristics in tumor cells of oral squamous cell carcinoma (OSCC) and to explore its relationship with lymph node metastasis (LNM).MethodsBy integrating single-cell data of OSCC from public databases, an expression matrix comprising 127,149 cells was constructed. Gene set scores were calculated using the irGSEA package, and GO and KEGG analyses were performed to identify enriched pathways. The R package monocle3 was employed to calculate the cell trajectory and infer evolutionary patterns. The MuSiC2 package was employed to enable the evaluation of cell proportions. Cell-cell interaction information was analyzed using the CellChat package. The expression of cathepsin V (CTSV), glutathione peroxidase 4 (GPX4), and cyclin-dependent kinase inhibitor 2A (CDKN2A) was validated via immunohistochemistry and multiplex immunohistochemistry in oral mucosa (OM), non-metastatic primary tumors (nPT), and metastatic primary tumors (mPT). Additionally, R package oncoPredict was utilized to identify potential drug sensitivities.ResultsThe malignant cells in OSCC were divided into five subtypes, among which Epi_2 existed more in mPT and had higher MCDR characteristics. In addition, Epi_2 enriched multiple malignant-related pathways such as HEDGEHOG, NOTCH, and MYC. The spatial transcriptome and bulk RNA data verified that the proportion of Epi_2 in mPT was higher than that in nPT. Cell communication analysis showed that the effect of Epi_2 on endothelial cells was enhanced, which was mainly reflected in VEGFR and CXCL signaling pathways. Immunohistochemical results showed that the expression of Epi_2 characteristic markers CTSV and GPX4 in mPT was significantly higher than that in nPT. Multiplex immunohistochemical results showed that the co-expression cells of CTSV, GPX4 and CDKN2A in mPT were more than those in nPT. OSCC patients with high Epi_2 characteristics may have immunotherapy resistance and anti-EGFR treatment resistance. Doramapimod was identified as a sensitive drug.ConclusionThere is a type of malignant cells with characteristics of MDCR in OSCC, which is related to LNM and treatment resistance. It provides a predictive marker for early diagnosis of LNM.